EEG Based Detection Of Epilepsy And Anesthetic Level Using Artificial Neural Networks - Vairavan, Srinivasan (2006)
The electroencephalogram (EEG) is a time-varying electrical signal recorded from electrodes placed on or inside the brain of human subject. EEG signal is a measure of the electrical activity of the brain which can be employed as a clinical tool for the diagnosis of many medical problems. The work carried out in this thesis primarily focuses on two important medical problems, namely, detection of epilepsy and detection of anesthetic depth levels.